Testing the Therapeutic Role of the Crude Alcohol Extract of the Onopordium acanthium Plant on Induced Eczema in White Rats - Kazem, Ali Mohammed Hussein (Majallat Jāmiʻat Bābil, 2025)
Background: The study examined the efficacy of the alcoholic extract of the plant Onopordium acanthium on acetone-induced eczema in white rats (Rattus norvegicus). The research aimed to investigate therapeutic alternatives for patients with chronic skin eczema, as the drugs currently used are associated with side effects that can be more severe than the disease itself. Materials and Methods: In the experiment, 40 male rats were used and divided into four groups, each consisting of 10 animals. The experiment lasted for 18 days, and the test was conducted on the animal's ear. The first group received distilled water, while the second group was treated with 5% acetone to induce eczema. The third and fourth groups were treated with the plant's alcoholic extract at concentrations of 100 µg/mL and 200 µg/mL, respectively, in addition to acetone as a control treatment group. Results: The results indicated a significant change (P ≤ 0.05) in skin thickness in the second group compared to the control group. It was also observed that there was a change in skin colour, losing its natural rosy hue and developing cracks with dryness. While there were no statistically significant differences (P ≤ 0.05) in the third and fourth groups that received the extract at concentrations of 100 and 200 µg/ml, with redness remaining, the dryness and skin cracks were less pronounced compared to the second group treated with acetone alone. While the change in ear weight showed negligible differences in the first group (control), statistically significant differences were observed in the second group. The third and fourth groups did not show any differences in ear weights when compared to the control. Conclusion: The thistle plant Onopordium acanthium is a medicinal plant that contains antioxidant compounds and exhibits anti-inflammatory effects, primarily in the treatment of skin diseases such as eczema. It helps reduce damage to the skin barrier and accelerates its repair. There is no significant toxicity of the plant towards skin cells at the applied concentration levels.